Bali Included as ‘No List 2020’, a Shocking news on the end of 2019 - Ida Bagus Putra Setiawan (Bali Tourism Journal, 2019)
A US-based tourism magazine ‘Fodor’ includes Bali as ‘No List 2020’. The news infuriated Bali Governor Wayan Koster. Koster presumed the action was an example of foul play in tourism competition. Meanwhile, Minister of Tourism and Creative Economy, Wishnutama Kusbandio claimed he did not bother with the Fodor's review. The news might be the Fodor’s strategy as a media to reach a wider audience. Fodor’s included Bali as "No List 2020" due to three major factors namely poor waste management, clean water existence, and foreign tourists’ disrespectful attitude. Findings showed what the media wrote apparently reflects the todays reality on th Island of Gods. However, the local Government has been starting to make significant improvement from waste management, and tourism standard. Tourism stakeholder in Indonesia especially Bali, might be infuriated by Fodor’s No List 2020. Rather than to negatively response to the news, it is better to consider it as positive feedback for Bali tourism. In addition, a good quality feedback from media as one of society control would be well appreciated if it is providing problem-solving solution instead of only focus on critics.